Principal Leadership Management in Improving Teacher Motivation at Assa'adah Bungah Vocational School, Gresik - Syifaul Aini; Qomaruddin Qomaruddin; Nur Fatih Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze school principal leadership management in increasing teacher motivation at SMK Assa’adah Bungah Gresik. This research uses a qualitative approach with a descriptive type. The research subjects include the school principal and teachers, with data collection techniques through observation, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results show that school principal leadership management at SMK Assa’adah Bungah Gresik is implemented through four management functions, namely planning that integrates vocational goals and Islamic values, organizing through clear division of tasks, actuating with democratic and exemplary leadership styles, and controlling in the form of coaching. Teacher motivation is driven by intrinsic factors in the form of spiritual awareness of teaching as worship, and extrinsic factors in the form of responsive leadership support. The integration of these managerial functions has proven effective in creating a conducive work climate and increasing teacher work motivation holistically in a pesantren-based vocational school environment. This research provides a theoretical contribution by strengthening the concept of principal leadership management based on the integration of Islamic values and the managerial function of POAC in improving teacher motivation. Practically, this research provides an implementation model for principals, particularly in Islamic boarding school-based vocational schools (SMK), in creating a conducive work climate and increasing teacher motivation in a sustainable manner.